DASAR PROGRAM PERENCANAAN DAN PERANCANGANARSITEKTUR (DP3A) PENGEMBANGAN LAPANGAN PANCASILA KOTA SALATIGA SEBAGAI URBAN PUBLIC SPACE YANG BERKELANJUTAN - MUNIB, M.ABDULLAH, Dr.Ir. Qomarun MM (2016)
Lapangan Pancasila Salatiga is a field in the city center as a place to socialize among Salatiga Salatiga and the surrounding communities. Field as one of the public space are still many shortcomings which should be available in a public space. Thus the method of direct observation Courses Pancasila, in order to know what are the shortcomings of existing, as well as any facilities required the local community as a complement various akivitas in Pancsila Field. Urban pubic space sustainable certified course is very suited to complement the existing deficiencies. Of course, with various architectural approach that fits the needs that exist